2022
DOI: 10.1021/acsomega.2c03218
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Separation of C-Tetramethylcalix[4]resorcinarene Conformers by Means of Reversed-Phase Solid-Phase Extraction

Abstract: A reversed-phase high-performance liquid chromatography (RP-HPLC) method was developed to study the conformer formation generated during the reaction for obtaining C-tetramethylcalix [4]resorcinarene. The chromatographic method was used to design a strategy for purifying the reaction products, using solid-phase extraction columns (RP-SPE) and gradient elution. The chromatographic profiles of the cyclocondensation reaction between resorcinol and acetaldehyde show the presence of three products under the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It has been reported that a single conformer or a conformational mixture can be obtained as a reaction product in the synthesis of this type of resorcinarene derivative [ 28 , 29 ]. To characterize the two principal products, a purification/separation and recrystallization process was carried out [ 30 ], and then each purified product was characterized via RP-HPLC, 1 H-NMR, and 13 C-NMR. A white solid was obtained, and its chromatographic profile shows a single species at 9.6 min with a purity of 96.4% ( Figure 2 b).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that a single conformer or a conformational mixture can be obtained as a reaction product in the synthesis of this type of resorcinarene derivative [ 28 , 29 ]. To characterize the two principal products, a purification/separation and recrystallization process was carried out [ 30 ], and then each purified product was characterized via RP-HPLC, 1 H-NMR, and 13 C-NMR. A white solid was obtained, and its chromatographic profile shows a single species at 9.6 min with a purity of 96.4% ( Figure 2 b).…”
Section: Resultsmentioning
confidence: 99%
“…Each single crystal example was grown with slow evaporation from the relevant isomer solution (1 mM). It should be noted that the corresponding macrocycle isomer has the structure that is similar to meso-substituted resorcinarene with chair ( 1 ), kite ( 2 ), or crown ( 3 ) comformation 35 . With the NMR spectroscopic study, the similarities were further verified.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it is used as a slipping technique in the production of rotaxane 17 , 27 , 33 . Some examples of thermal-induced conversion between two forms are achieved 28 , 34 , 35 . However, some biomacromolecules have been found to have more than two distinct stable or metastable folding configurations.…”
Section: Introductionmentioning
confidence: 99%